2017
DOI: 10.1136/gutjnl-2017-314418
|View full text |Cite
|
Sign up to set email alerts
|

Prebiotic galacto-oligosaccharides mitigate the adverse effects of iron fortification on the gut microbiome: a randomised controlled study in Kenyan infants

Abstract: Objective Iron-containing micronutrient powders (MNPs) reduce anaemia in African infants, but the current high iron dose (12.5 mg/day) may decrease gut Bifidobacteriaceae and Lactobacillaceae, and increase enteropathogens, diarrhoea and respiratory tract infections (RTIs). We evaluated the efficacy and safety of a new MNP formula with prebiotic galactooligosaccharides (GOS) combined with a low dose (5 mg/ day) of highly bioavailable iron.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
159
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 145 publications
(171 citation statements)
references
References 37 publications
12
159
0
Order By: Relevance
“…A potential advantage of a lower 5-mg Fe dose with higher fractional absorption would be that w50% lower amounts of unabsorbed iron would reach the infant colon, which may lessen the chance for gut dysbiosis, inflammation, and diarrhea (4,5). Moreover, a recent intervention trial in Kenyan infants reported that the addition of GOS to an iron-containing MNP can mitigate the adverse effects of iron by enhancing the growth of bifidobacteria and lactobacilli and reducing abundances of enteropathogens (14). (27).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A potential advantage of a lower 5-mg Fe dose with higher fractional absorption would be that w50% lower amounts of unabsorbed iron would reach the infant colon, which may lessen the chance for gut dysbiosis, inflammation, and diarrhea (4,5). Moreover, a recent intervention trial in Kenyan infants reported that the addition of GOS to an iron-containing MNP can mitigate the adverse effects of iron by enhancing the growth of bifidobacteria and lactobacilli and reducing abundances of enteropathogens (14). (27).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is likely that the total amount of iron that was absorbed from our 5-mg dose (w0.9 mg) would be comparable to the iron that would be absorbed from MNPs containing 12.5 mg and would cover the total iron need of 0.69 mg/d in 6-12-mo-old infants (39). In a recent randomized 4-mo trial in Kenyan infants, an MNP containing 5 mg Fe as FeFum+NaFeEDTA increased hemoglobin and reduced anemia (14). A potential advantage of a lower 5-mg Fe dose with higher fractional absorption would be that w50% lower amounts of unabsorbed iron would reach the infant colon, which may lessen the chance for gut dysbiosis, inflammation, and diarrhea (4,5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the infant colon, these effects may provide a less-favorable growth environment for enteric pathogens and enhance the commensal barrier against colonization by pathogens (28,29). A recently completed intervention trial in Kenyan infants has demonstrated that addition of GOSs to an MNP containing 5 mg Fe (2.5 mg as ferrous fumarate and 2.5 mg as NaFeEDTA) effectively reduces anemia and mitigates many of the adverse effects of the iron on the gut microbiome (62).…”
Section: Strategies To Balance Need For Iron and Risk Of Adverse Effectsmentioning
confidence: 99%
“…Considering the above, the level of iron in the gut can be manipulated to prevent the outgrowth of pathogens. For instance, the co-supplementation of iron and GOS to anaemic Kenyan infants has been shown to increase iron absorption, thereby mitigates the adverse effects of iron on the gut microbiota (Paganini et al 2017b). The abundances of Bifidobacterium and Lactobacillus spp.…”
Section: Microbiota-targeted Nutrientsmentioning
confidence: 99%